Petrogenesis of Late Triassic intrusive rocks in the northern Liaodong Peninsula related to decratonization of the North China Craton: Zircon U–Pb age and Hf–O isotope evidence - Yang, J.; Sun, J.; Zhang, J.; Wilde, Simon (Elsevier BV, 2012)
Major and trace element, whole rock Sr‐, Nd‐and Hf‐isotopes and zircon U–Pb age and Hf–O isotope data have been determined for mafic to felsic intrusive rocks from the Late Triassic Mayihe (MYH), Longtou–Chaxinzi–Xiaoweishahe (LCX) and Nankouqian–Xidadingzi (NX) intrusions in the northern Liaodong Peninsula, NE China, in order to investigate their sources and petrogenesis related to decrationization of the North China Craton. The rocks include clinopyroxene diorite, monzodiorite, quartz diorite, granodiorite, monzogranite and mafic microgranular enclaves. Laser ablation inductively coupled plasma mass spectrometry (LA–ICPMS) and secondary ion mass spectrometer (SIMS) U–Pb analyses of zircon from MYH, LXC to NX intrusions yield Late Triassic ages of 224–218 Ma, establishing that the mafic and felsic magmas were coeval. The clinopyroxene diorites from the MYH pluton have high MgO concentrations at low silica contents, with positive whole rock εNd(t) (up to + 3.8) and εHf(t) (up to + 6.2) and zircon εHf(t) values and some mantle-like δ18O values. They are enriched in large ion lithophile (LILEs) and light rare earth elements (LREEs) and depleted in high field strength elements (HFSEs), which can be explained as melts derived from a depleted mantle, with some subsequent crustal contamination.However, the diorites from the LXC and NX intrusions are high‐K rocks and have high MgO concentrations and mantle-like δ18O values, but with negative whole rock εNd(t) (− 12.9 to − 7.6) and εHf(t) (− 14.0 to − 5.6) and zircon εHf(t) values, distinct from those of MYH pyroxene diorites, indicating that their parental magmas were derived from partial melting of an ancient lithospheric mantle. The granitoids from three plutons have high SiO2 contents and low MgO concentrations, suggesting they were mainly derived from crustal sources. However, the MYH monzogranite and granodiorite have positive whole rock εNd(t) and εHf(t) (up to + 3.0) and zircon εHf(t) values, indicating a juvenile crustal source, whereas, the LXC and NX granitoids have strong negative and variable whole rock εNd(t) and εHf(t) and zircon εHf(t) values, indicating that they were derived from partial melting of ancient lower crustal materials with involvement of mantle components. Field observations, geochronology, geochemistry, Sr–Nd–Hf isotopic and zircon Hf–O isotopic compositions point to a complex petrogenesis, where mantle- and crust-derived magma mixing was coupled with crystal fractionation, thus explaining the genetic link between mafic and felsic rocks. Identification of four components, i.e., depleted and enriched mantle and juvenile and ancient crust in the Late Triassic magmatism in the northern Liaodong Peninsula suggests a strong mantle–crust interaction process related to decratonization of the North China Craton.